Social Entrepreneurship and Creativity: Building an Innovation Ecosystem for Solving Social and Environmental Issues - Pilifus Junianto; D Yadi Heryadi; Prety Diawati (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Social and environmental issues are increasingly pressing to be addressed in this modern era. Social entrepreneurship has emerged as a promising solution in tackling these social and environmental challenges. This research aims to delve into the relationship between creativity and social entrepreneurship, and how creativity can be a primary driver in generating innovative solutions to social and environmental problems. This research employs a qualitative approach with descriptive and narrative analysis through literature review. Data were obtained from Google Scholar sources spanning from 2020 to 2023. The study findings indicate that social entrepreneurship and creativity are two concepts with great potential to transform paradigms in developing innovation ecosystems aimed at solving social and environmental issues. Both bring forth the notion that business can not only be a tool for seeking profit but also a means to create positive change in society and the surrounding environment. Social entrepreneurship involves business efforts aimed at addressing social and environmental issues with innovative and sustainable approaches. This differs from conventional businesses that primarily focus on profitability. Social entrepreneurship encourages entrepreneurs to consider the social and environmental impact of their business activities and seek sustainable solutions to the problems faced by society. On the other hand, creativity becomes key in building an effective innovation ecosystem for solving social and environmental problems.